Recent advances in select interventional approaches to cancer-related pain. (November 2013) - Chai, Thomas; Smith, Lance S; Gebhardt, Rodolfo
SUMMARY Interventional approaches for cancer-related pain have demonstrated utility and safety as a component of multimodal pain management. A number of techniques have been developed and implemented to manage the variety of cancer pain conditions and syndromes that exist as a result of the underlying malignant process and its associated oncologic treatment. These procedural pain modalities continue to evolve with advances in experience, understanding and technology in the field. Neurostimulation, vertebral augmentation with stabilization and intrathecal drug delivery, are prime examples of innovative approaches in interventional pain medicine for cancer pain with continued improvement in design to better achieve adequate analgesia and reduce risk. The intent of this article is to describe the aforementioned interventions and recent developments pertaining to them.